Design of PID Control System Assisted using LabVIEW in Biomedical Application - Arsad, N.; Ariffin, N. H. (Journal of Advanced Research in Applied Mechanics, 2020)
Temperature variation of modern incubator produced inaccuracy and aging. This causes problem in maintaining temperature at a required level. Thus, overheating will damaging and interrupt data under measured. In order to maintain the temperature at a require level, an economical and reliable of a Proportional, Integral and Derivative (PID) acquisition control system assisted using LabVIEW has been developed. The PID acquisition control system uses feedback from the temperature sensor to calculate and vary converted voltage to heat a heating element at a required level. Results show that, the PID acquisition control system able to control the temperature at the required level of 38 °C.